Medical Management of COVID-19: Evidence and Experience - Subhasish Bose; Sreedhar Adapa; Narothama Reddy Aeddula; Sasmit Roy; Deepak K. Nandikanti; Phani Mohan Vupadhyayula; Srikanth Naramala; Vijay Gayam; Vijayadershan Muppidi; Venu Madhav Konala (2020)
Coronavirus disease 2019 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and this infectious disease is termed COVID-19 in short. On a global scale, as of June 1, 2020, the World Health Organization (WHO) published statistics of 6,057,853 infected patients and 371,166 deaths worldwide. Despite reported observational data about the experimental use of certain drugs, there is no conclusively proven curative therapy for COVID-19 as of now; however, remdesivir received emergency use authorization (EUA) by the Food and Drug Administration (FDA) recently for use in patients hospitalized with COVID-19. There are several ongoing clinical trials related to the pharmacological choices of therapy for COVID-19 patients; however, drug trials related to observational studies so far have yielded mixed results and therefore have created a sense of confusion among healthcare professionals (HCPs). In this review article, we seek to collate and provide a summary of treatment strategies for COVID-19 patients with a variable degree of illness and discuss pharmacologic and other therapies intended to be used either as experimental medicine/therapy or as part of supportive care in complicated cases of COVID-19. J Clin Med Res. 2020;12(6):329-343 doi: https://doi.org/10.14740/jocmr4201